Extraction and Determination of Polyphenols in Dry Olive Leaves using Ultrasound Apparatus (Latakia University Journal -Basic Sciences Series, 2018)
Total Polyphenol was studied in olive leaves collected from Lattakia area (AlQurdaha zone), where Phenolic compounds were extracted from dry Olive leaves by using two extraction methods: maceration and Ultrasonic Device. By the both two methods a study was carried out on the extraction solvent concentration effect where the extraction was done by using the mixture of Ethanol-Water with different percentages        (60,70,80 %). As well, The extraction temperature effect was studied at the both methods at (20,30, 40°C); in addition to the study of the extraction time effect.At the method of Maceration Extraction, the total polyphenols amount was studied in dry olive leaves after extraction during different times (24,48,72 h). While at the Ultrasonic Extraction the times were (10,20,30 min).The study showed that the highest amount of phenolic compounds were existed in dry olive leaves which were extracted by Ultrasonic Waves with the concentration of the solvent ethanol-water 80%, temperature of 40°C, and with an extraction time of 20min.